Pengambilan Keputusan Multi Hesitant N-Soft Sets - Fatia Fatimah (Ikatan Ahli Informatika Indonesia (IAII), 2020)
In this article, we introduce a new hybrid model of -soft sets called multi hesitant -soft sets (MHNSS). The multi hesitant -soft sets is extention of -soft sets theory which is needed for multicriteria from some group decision makers. We propose the decision making algorithm of MHNSS dan apply it with real life data of distance education especially online learning using webinar tutorial. The population are tutors of Universitas Terbuka Padang that using webinar tutorial between April until May 2020. We use random sampling and spread questionnaires online to collect the data. As a result, by using the MHNSS algorithm, we conclude that webinar tutorial is effective for conceptual subjects.